Healthcare providers' perspectives on sustaining respectful maternity care appreciated by mothers in five hospitals of Rwanda - Alice Muhayimana; Irene Kearns (BMC, 2024)
Abstract Background Childbirth reserves respect, as emphasized by the World Health Organization in 2018, and the focus towards the need for positive, dignified delivery experiences has become an integral aspect of Respectful Maternity Care (RMC). It is a known fact that RMC is pivotal for favourable birth outcomes and contributes to the satisfaction of maternity care. The absence of RMC negatively affects women's and newborns' rights. The study aimed to explore healthcare providers' perspectives on sustaining RMC actions that mothers previously reported. Methodology This study was conducted in five hospitals in the Eastern province of Rwanda, involving 5 Focus Group Discussions (FGDs) with midwives and nurses. For interviews, we purposively selected 5-unit managers and five physicians. Additionally, 40 midwives and nurses were recruited for the FGDs. The research utilized the Dream phase of Appreciative Inquiry (AI) for interviews and Focus Groups. Data collection aimed to gain insights into Healthcare Providers' perceptions of how RMC is provided and how to establish and sustain RMC in Rwandan health facilities. Nvivo 12 was employed for organizing codes and creating a codebook, and thematic analysis was applied. Results Four themes with sub-themes emerged. Namely, 1) Women-centered care, with Compassionate care, Privacy and confidentiality maintenance, Information provision and Liberty in decision making, Effective communication, Family involvement, Cleanliness, and Equality care. 2) Professionalism compliance with Motivated staff, Teamwork, Continuous development, Quality work provision, and Community trust. 3) RMC encounters 4) RMC sustenance. Conclusion and recommendations The continuous pursuit of high RMC standards in Rwanda involves improving childbirth experiences through utilizing existing resources, ongoing improvement, and sustaining achievements. Key recommended actions in this study for sustaining RMC encompass promoting women-centred care, enhancing healthcare provider attitudes, ensuring professionalism, building community trust, maintaining conducive health facility environments, and involving leadership.